Millet bread and pulse dough from early Iron Age South India: Charred food lumps as culinary indicators. (January 2022) - Bates, Jennifer; Wilcox Black, Kelly; Morrison, Kathleen D.
Abstract: Food lumps are becoming an increasingly important part of the 'foodways' turn in archaeobotanical analysis. These amalgams of plant materials allow insights into more than the taxa lists of plants used or even just present on a site; they represent how people engaged with and created food items out of plants, in turn shining a light on notions of food processing, preparation and cooking techniques and culinary traditions. Food lump analysis has traditionally been focused on the Near East and Europe, where large grained cereals have dominated the archaeobotanical discussion. This paper instead represents an analysis of more complex food practices, that of the Southern India Iron Age, where millets and pulse foods were an important part of the culinary tradition. Through a preliminary analysis of lumps from Feature 40, an Iron Age pit, at the site of Kadebakele in southern Deccan, we demonstrate that people were using both millets and pulses to make food items through a variety of culinary techniques and technologies, from dry doughs to wet batters. This preliminary analysis highlights the complexity of food lump analysis in regions outside the Near East and Europe and asks us to think about the longevity of culinary practices in South India. Highlights: First study of charred food lumps in Asia. Millet and pulse were used to make a variety of doughs and batters. Millet flatbread is suggested, but may have been part of a multi-seeded dough. Pulse batter is also indicated in some lumps. It also suggests that a diversity of cooking/preparatory methods for food were being used by South Indian Iron Age peoples. Highlights role of food lump analysis in future research globally.